2018
DOI: 10.1016/j.bar.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating for survival: Balancing mission and money

Abstract: The impetus for prioritising money over mission in charities is increasingly pertinent as public sector austerity progresses in the UK. Mid size charities-who are heavily reliant on grant funding-have experienced proportionately greater challenges to austerity than larger entities. A substantial part of accountability efforts in mid size charities are directed towards funders, where funder imposed frameworks and measures may direct charity attention away from social mission towards funder needs, causing missio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…This both highlights the influence of socio-economic factors on the evolution of PMSs, and the power of salient external stakeholders to divert focus from what might be seen as key mission objectives within the organisation (and by the general public). Similar funding pressures were examined in much smaller organisations in Scotland (Henderson & Lambert, 2018). Again the influence of funders was evidenced, along with the susceptibility to mission drift in the budget-constrained environment, as was the influence of key funders on the evolution of the PMSs.…”
Section: Performance Managementmentioning
confidence: 79%
“…This both highlights the influence of socio-economic factors on the evolution of PMSs, and the power of salient external stakeholders to divert focus from what might be seen as key mission objectives within the organisation (and by the general public). Similar funding pressures were examined in much smaller organisations in Scotland (Henderson & Lambert, 2018). Again the influence of funders was evidenced, along with the susceptibility to mission drift in the budget-constrained environment, as was the influence of key funders on the evolution of the PMSs.…”
Section: Performance Managementmentioning
confidence: 79%
“…NFPs' resource constraints are a continual challenge (Irvine, 2010;Valentinov, 2010) as they face a more diffuse and complex political environment than businesses. Donors' expectations and government scrutiny of NFPs' tax-exempt status, along with funders' requirements, add to operational challenges (Henderson & Lambert, 2018;Renz & Herman, 2016). When contrasting FPs and NFPs, it has been found that NFPs exhibit greater diversity in the services offered, their missions, consumers and stakeholders (Beck, et al, 2008).…”
Section: The Nfp Environmentmentioning
confidence: 99%
“…They offer a greater diversity of services at prices often below market values (Beck, Lengnick‐Hall, & Lengnick‐Hall, 2008). Nonprofits often rely on donations and grants to supplement their revenue while they simultaneously face pressure to prioritize finances over mission due to public sector austerity measures (Henderson & Lambert, 2018). The aforementioned nonprofits’ characteristics exacerbate the financial constraints under which they operate.…”
Section: Theory and Literaturementioning
confidence: 99%